Topical administration of Curcuma longa L. extract gel increases M2 macrophage polarization and collagen density in skin excision - Afiat Berbudi&, Hendi Anshori, Andromeda Andromeda, Alexander Kwarteng, Almahitta Cintami Putri, Nur Atik (Journal of Applied Pharmaceutical Science, 2021)
While M1 macrophages initiate wound healing by inducing the inflammation phase, M2 macrophages are crucial in the proliferation phase by producing growth factors that accelerate new tissue formation. Turmeric (Curcuma longa L.) is known to accelerate wound closure; however, mechanisms underlying the wound healing properties of C. longa L. remain to be documented. Therefore, this study investigated the mechanisms by which C. longa L. accelerates wound healing. Here, an experimental study was conducted using 30 male Swiss Webster mice. Curcuma longa L. extract was applied on the wound bed tissue starting on day 3 after wound induction. The Arginase-1 (Arg-1) and inducible nitric oxide synthase (iNOS) (M1 and M2 markers) gene expressions from wound skin tissue were analyzed, while collagenesis during tissue repair was observed by histopathology analysis of excised skin on day 6 after wound induction. Upregulation of Arg-1 in the treated group was observed on day 6 after wound induction compared to the positive control (p = 0.0394) and the negative control groups (p = 0.0313). In addition, the Arg-1/iNOS ratio revealed a significant increase of M2 polarization in the C. longa L.-treated wound compared to negative controls (p < 0.0001), but not significant when compared with positive controls (p = 0.0535). Similarly, collagen density was significantly higher in the C. longa L.-treated wound than the negative control (p = 0.0418) and the positive control (p < 0.0001). These results suggest that administration of C. longa L. extract gel improved wound tissue repair on skin excision by inducing M2 polarization on wound tissue during healing.
Keywords: Curcuma longa L., turmeric rhizome extract, curcumin, M2 macrophage polarization, topical gel.